Low Temperature Stress Alters the Expression of Phytoene Desaturase Genes (crtP1 and crtP2) and the ζ-Carotene Desaturase Gene (crtQ) Together with the Cellular Carotenoid Content of Euglena gracilis. (22nd October 2018) - Kato, Shota; Tanno, Yuri; Takaichi, Shinichi; Shinomura, Tomoko
Abstract: Carotenoids participate in photosynthesis and photoprotection in oxygenic phototrophs. Euglena gracilis, a eukaryotic phytoflagellate, synthesizes several carotenoids: β-carotene, neoxanthin, diadinoxanthin and diatoxanthin. Temperature is one of the most striking external stimuli altering carotenoid production. In the present study, to elucidate the regulation of carotenoid synthesis of E. gracilis in response to environmental stimuli, we functionally identified phytoene desaturase genes ( crtP1 and crtP2 ) and the ζ-carotene desaturase gene ( crtQ ) of this alga and analyzed expression of those genes and the composition of major carotenoids in cells grown under cold (20C) and high-intensity light (HL; 240 mol photon m −2 s −1 ) conditions. 20C–HL treatment increased the transcriptional level of the phytoene synthase gene ( crtB ), and crtP1 and crtP2, whose products catalyze the early steps of carotenoid biosynthesis in this alga. Cultivation at 20C under illumination at 55 mol photon m −2 s −1 (low-intensity light; LL) decreased the cell concentration, Chl and total major carotenoid content by 61, 75 and 50%, respectively, relative to control (25C–LL) cells. When grown at 20C–HL, the cells showed a greater decrease in cell concentration and photosynthetic pigment contents than those in 20C–LL. β-Carotene, neoxanthin and diadinoxanthin contents were decreased by more than half in 20C–LL and 20C–HL treatments. On the other hand, when subjected to 20C–LL and 20C–HL, the cells retained a diatoxanthin content comparable with control cells. Our findings suggested that diatoxanthin plays crucial roles in the acclimation to cold and intense light condition. To the best of our knowledge, this is the first report on a photosynthetic organism possessing dual crtP genes.